Why Do Patients and Caregivers Seek Answers From the Internet and Online Lung Specialists? A Qualitative Study - Schook, Romane Milia; Linssen, Cilia; Schramel, Franz MNH; Festen, Jan; Lammers, Ernst; Smit, Egbert F; Postmus, Pieter E; Westerman, Marjan J (JMIR Publications, 2014)
BackgroundSince its launch in 2003, the Dutch Lung Cancer Information Center's (DLIC) website has become increasingly popular. The most popular page of the website is the section "Ask the Physician", where visitors can ask an online lung specialist questions anonymously and receive an answer quickly. Most questions were not only asked by lung cancer patients but also by their informal caregivers. Most questions concerned specific information about lung cancer. ObjectiveOur goal was to explore the reasons why lung cancer patients and caregivers search the Internet for information and ask online lung specialists questions on the DLIC's interactive page, "Ask the Physician", rather than consulting with their own specialist. MethodsThis research consisted of a qualitative study with semistructured telephone interviews about medical information-seeking behavior (eg, information needs, reasons for querying online specialists). The sample comprised 5 lung cancer patients and 20 caregivers who posed a question on the interactive page of the DLIC website. ResultsRespondents used the Internet and the DLIC website to look for lung cancer-related information (general/specific to their personal situation) and to cope with cancer. They tried to achieve a better understanding of the information given by their own specialist and wanted to be prepared for the treatment trajectory and disease course. This mode of information supply helped them cope and gave them emotional support. The interactive webpage was also used as a second opinion. The absence of face-to-face contact made respondents feel freer to ask for any kind of information. By being able to pose a question instantly and receiving a relatively quick reply from the online specialist to urgent questions, respondents felt an easing of their anxiety as they did not have to wait until the next consultation with their own specialist. ConclusionsThe DLIC website with its interactive page is a valuable complementary mode of information supply and supportive care for lung cancer patients and caregivers.